Using Windows Azure Mobile Services to Cloud-Enable your Windows Store Apps in JavaScript (Windows Azure Developer Center) (Microsoft, 2015)
This section shows you how to use Windows Azure Mobile Services and JavaScript to leverage data in a Windows Store app. In this tutorial, you will download an app that stores data in memory, create a new mobile service, integrate the mobile service with the app, and then login to the Windows Azure Management Portal to view changes to data made when running the app.